2019
DOI: 10.5530/pj.2019.11.96
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Property of Mussaenda philippica

Abstract: Introduction: Mussaenda philippica (Rubiaceae) is a shrub distributed in all the planes of India, Philippines and SouthEast Asia. Its synonyms are M. grandiflora, M. acutifolia, M. frondosa etc. The plant is preferred as medication for the treatment of jaundice, dysentery, stomachache and influenza. The current study was based on the evaluation of antiulcer property of M. philippica leaves extract. Methods: The methods used were pylorus ligated, ethanol induced and 0.2(M) NaOH induced ulcer in rats. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Both chloroform and ethyl acetate extract inhibited Escherichia coli, while both ethyl acetate and ethanol extract inhibited Salmonella enteritidis. Aqueous extract of M. philippica leaves demonstrated potential antiulcer activity in experimental rat models (Jena et al 2019).…”
Section: Phytochemistrymentioning
confidence: 98%
See 2 more Smart Citations
“…Both chloroform and ethyl acetate extract inhibited Escherichia coli, while both ethyl acetate and ethanol extract inhibited Salmonella enteritidis. Aqueous extract of M. philippica leaves demonstrated potential antiulcer activity in experimental rat models (Jena et al 2019).…”
Section: Phytochemistrymentioning
confidence: 98%
“…The plant parts of M. philippica are traditionally used in various folkloric medicine as a treatment for gastrointestinal disorders (Jena et al 2019). Sophy et al (2015) reported the medicinal use of M. philippica in India and other South Asian countries.…”
Section: Local Medicinal Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to its organotoxic nature and negligible effect on decreasing blood pressure, the Bryophyllum pinnatum leaf extract is ineffective as an antihypertensive medication. 34 Rat wound models were utilised to evaluate pinnatam's efficacy in healing wounds. According to the histological analysis, it has shown good potential against wound.…”
Section: Isolation Of Active Compounds From Ee Of Bryophyllum Pinnatu...mentioning
confidence: 99%